Pemanfaatan Bak Depurasi Yutuk (Undur – Undur Laut) di Desa Widarapayung Wetan Sebagai Upaya Menjaga Keamanan Pangan - Kristiningsih, Ari; Wittriansyah, Khoeruddin; Purwaningrum, Santi; Prasetya, Nur Wachid Adi; Wanti, Linda Perdana; Hastuti, Hety Dwi; Ariawan, Radhi; Sarihidaya, Nur Akhlis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2023)
Yutuk, which is also known as undur - undur laut, is a typical souvenir from Widarapayung Wetan beach. The handling of yutuk before consumption by community groups processing yutuk is still in a simple way by soaking it in a bucket or tub. Depuration of yutuk or shellfish makes the dirt contained in the organs of the body come out and can reduce the heavy metal content contained therein. This Community Service activity aims to increase the education of yutuk processing groups to use the depuration method with a special yutuk tub with a recirculation system that uses natural filters such as ginger coral, zeolite and activated charcoal. The Community Service activity stage begins with interviews and field observations and then continues with a Focus Group Discussion (FGD) and then implements a yutuk depuration tub for the yutuk processing group in Widarapayung Wetan village. Through Community Service activity, the yutuk processing community groups are equipped with good and correct depuration techniques so that they can be achieved properly and the community can consume them safely and comfortably.